Evaluation of phototoxic effects of chlorquine and eleven other antimalarials in mice - YUAN Bo-jun; LI Bao-chun; SHEN Nian-ci (Acta Pharmacologica Sinica; Vol 7, No 5 (September 1986): Acta Pharmacologica Sinica, 2016)
The phototoxicity of anti-malarials was studied in mice that were irradiated for 24 h with black light in 22+/-1 degrees. No phototoxicity was observed within 7 d in mice after: 1) ig 1/4 LD50 with 12 antimalarials (chloroquine phosphate, piperaquine phosphate, hydroxypiperaquine phosphate, quinine sulfate, mefloquine hydrochloride, cycloquine hydrochloride, mequinacrine hydrochloride, artesunate (sodium dihydroartemisinin succinate), pyronaridine phosphate, cyclochloroquanide hydrochloride, pyrimethamine, primaquine phosphate); 2) iv 1/2-1/4 LD50 with the former 4 drugs; 3) ip 1/8 LD50 qd*7 d with the former 5 drugs.